Advancing understanding of autoimmune diseases and lung cancer: trends, themes, and future directions - Hao-Han Rao; Wan-Chen Xie; Feng Guo; Huan-Wen Chen (Discover Oncology)
Abstract Purpose Autoimmune diseases are closely linked with lung cancer (LC), forming a complex bidirectional relationship that poses significant challenges to treatment. A bibliometric analysis was conducted to investigate global research trends, key hotspots, and potential future directions in this field. Methods This study utilized bibliometric methods, analyzing 1161 publications from the Web of Science database spanning the years 1980 to 2024. Visualization and analysis were performed using tools such as VOSviewer, CiteSpace, and the bibliometrix R package. Results The dataset encompassed research from 73 countries, 1860 organizations, and 6734 authors, published in 541 sources. The United States emerged as the leading contributor in terms of publication output, with the Mayo Clinic identified as the most productive institution. The Cureus Journal of Medical Science published the highest number of articles, whereas Chest garnered the most citations. Among individual researchers, Sasha Bernatsky stood out as the most prolific and frequently co-cited author. Keyword analysis revealed significant focus areas, including immune therapy-related adverse events, interstitial lung disease, comorbidities, diagnostic methods, and autoantibodies in paraneoplastic syndromes. Emerging research priorities center on understanding immune mechanisms, addressing comorbidities, and advancing diagnostic approaches. Conclusion This bibliometric study provides a comprehensive overview of research trends and gaps in the intersection of autoimmune diseases and LC. It highlights the importance of exploring immune therapy mechanisms, managing comorbidities, and optimizing diagnostic strategies as key areas for future investigation.